e-Governance, citizen satisfaction and net benefits: the moderating effect of digital divide - Surya Bahadur G. C.; Santosh Kumar Gurung; Subarna Bir Jung Bahadur Rana; Bharat Ram Dhungana (Cogent Business & Management, 2024)
This article aims to analyze the influence of three e-Governance information system (IS) quality dimensions – information, system and service quality on usage intention, citizen satisfaction and net benefits in Nepal and assess the moderating role of digital divide on the relationship. It contributes by integrating digital divide in the DeLone and McLean (D&M)'s IS success model (ISSM). The study is based on a cross-sectional field survey of 304 e-Governance platform users located in both rural and urban municipalities in Nepal. The analysis was undertaken through PLS-SEM using the SmartPLS version 4.0. The results of the study revealed that e-Governance system quality and service quality have positive influence on citizen satisfaction. Likewise, intention to use is also found to have positive impact on citizen satisfaction. Additionally, the study finds that usage intention and citizen satisfaction affect net benefits positively. Further analysis indicated that digital divide interacts positively on relationship between the three IS quality dimensions and citizen satisfaction. This study contributes to prior literature in area of e-Governance by providing further insights into citizen satisfaction and net benefits of e-Governance. The implications offer directions on how policymakers can enhance citizen satisfaction and net benefits of e-Governance platforms through improvements in system and service quality as well as undertaking measures to address digital divide.
Keywords: C55; H11; H83; 033; 038; 650; Information system quality; e-governance; digital divide; citizen satisfaction; net benefits